Ceramides and risk of major adverse cardiovascular events: A meta-analysis of longitudinal studies - Mantovani, Alessandro; Dugo, Clementina (Journal of clinical lipidology, 2020)
Recent cohort studies evaluated the association between some previously identified high-risk ceramides [Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/22:0), Cer(d18:1/24:0) and Cer(d18:1/24:1)] and risk of major adverse cardiovascular events in adult population. The objective of this meta-analysis was to investigate the magnitude of such associations. We searched publication databases using appropriate keywords to identify cohort studies (published up to July 30, 2019), in which association between previously identified high-risk ceramides and major adverse cardiovascular events was reported. Data from eligible studies were extracted and meta-analysis was performed using random-effects modeling. Seven cohort studies with aggregate data on 29,818 individuals (2736 new cases of cardiovascular events over a median follow-up of 6 years) were included. Higher plasma levels of Cer(d18:1/16:0) (random effects hazard ratio [HR] per standard deviation 1.21, 95% confidence interval [CI] 1.11–1.32, I2 = 88%), Cer(d18:1/18:0) (HR 1.19, 95% CI 1.10–1.27, I2 = 68%), and Cer(d18:1/24:1) (HR 1.17, 95% CI 1.08–1.27, I2 = 83%) were associated with major adverse cardiovascular events. Conversely, no association with plasma levels of Cer(d18:1/22:0) (HR 1.14 95% CI 0.88–1.47, I2 = 88%) and Cer(d18:1/24:0) (HR 0.97, 95% CI 0.89–1.05, I2 = 73%) was found. Subgroup analyses did not substantially modify the findings. Higher plasma levels of Cer(d18:1/16:0), Cer(d18:1/18:0) and Cer(d18:1/24:1) were associated with major adverse cardiovascular events, whereas plasma levels of Cer(d18:1/22:0) and Cer(d18:1/24:0) were not. Additional research is required to elucidate the different role of ceramides on pathways involved in cardiovascular disease. •The magnitude of the association between ceramides and CVD remains uncertain.•Cer16, Cer18, and Cer24:1 were associated with CVD.•No association with Cer22 and Cer24:0 was observed.